2020
DOI: 10.1002/pri.1872
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of workplace mentoring preferences of new‐graduate physiotherapists within Australian practice

Abstract: Background and Purpose The transition from student to physiotherapist involves a steep learning curve typically characterised by stress, anxiety and a lack of confidence in clinical and professional skills. Workplace mentoring is widely used to mediate this transition. The aim of this study was to explore new‐graduate physiotherapists' preferences for workplace mentoring and perceived characteristics of effective mentoring to mediate workplace transition. Methods A qualitative study with a general inductive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Informal PD was identified as a main source to provide new graduates with a larger skillset and increased confidence in managing unfamiliar situations. These findings are congruous with literature, with new-graduate physiotherapists reporting the value of having an individualised and supportive mentor (Forbes et al, 2021). This previous research further supports that with appropriate guidance and reassurance, new graduates were able to have a sense of ownership over their career development while feeling welcomed and supported within their new workplace (Forbes et al, 2021).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Informal PD was identified as a main source to provide new graduates with a larger skillset and increased confidence in managing unfamiliar situations. These findings are congruous with literature, with new-graduate physiotherapists reporting the value of having an individualised and supportive mentor (Forbes et al, 2021). This previous research further supports that with appropriate guidance and reassurance, new graduates were able to have a sense of ownership over their career development while feeling welcomed and supported within their new workplace (Forbes et al, 2021).…”
Section: Discussionsupporting
confidence: 56%
“…These findings are congruous with literature, with new-graduate physiotherapists reporting the value of having an individualised and supportive mentor (Forbes et al, 2021). This previous research further supports that with appropriate guidance and reassurance, new graduates were able to have a sense of ownership over their career development while feeling welcomed and supported within their new workplace (Forbes et al, 2021). New graduates reflected on what they perceived to be adequate mentoring and PD within the hospital setting, specifically when considering skill development for managing complex and unfamiliar conditions.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, this study advocates for employers of new graduate physiotherapists to ensure appropriate support is provided to graduates during the transition from student to clinician. This support from senior clinicians is actively sought by new graduates and is supported by previous research into new graduate mentorship (Forbes et al 2021). Further research into the preparation for and support of new graduate physiotherapists in the hospital setting is warranted, given the multi-faceted roles of physiotherapists in this context.…”
Section: Discussionmentioning
confidence: 99%
“…New graduates transitioning from student to clinician face unique challenges as they commence professional practice and workplace support during this time (Forbes et al 2021). Stoikov et al (2020) identified that new graduates in hospital settings are particularly challenged by the increased caseload volume and complexity of their roles compared to the protected workloads they experienced as students (Stoikov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Time and tools to uncover and modify relevant psychological obstacles for recovery were perceived challenging and partly dependent on clinical experience. Another recent study found that newly graduated physiotherapists wanted accessible and individualized mentoring (Forbes et al., 2021). This may imply that tools, techniques and procedures for addressment of psychosocial obstacles for recovery should be included in basic as well as postgraduate curriculums for physiotherapists.…”
Section: Discussionmentioning
confidence: 99%